Public Relations in Service Sector and Corporate Image Management: A Research in Transportation Sector - Selin, Ünal Çimçek (European Scientific Journal, ESJ, 2017)
Because of the services having the features of being human-centered, consumed when they are produced and not able to be stocked; the institutions should give more importance to the works of public relations, use the media communication intensively; maintain and improve their image they should do this permanently. The image of an institution that the companies and organizations reflect out, has a vital importance in its relations with the public. Public relations give reputation to the image of an institution. Public relations have the major responsibility in creation, protection, and consolidation of an institution's image. Under the scope of our work, it is discussed how the public relations studies; that we think it is not used intensively, affect the corporate image and especially on the necessity of public relations methods and techniques to be used by the enterprises to create a corporate image operating in service sectors. As a field research, the in-depth interview was made with the Marketing Manager of Pamukkale Tourism in the transportation sector, which is one of the leading on road public transportation companies, on to what extent they use the advantage of public relations activities on creating a corporate image. As a result of research, we reached the conclusion that Pamukkale Tourism take the advantage of social media with public relations studies, especially considering the investments they made on social media, they used the public relations methods about customer satisfaction and providing a service quality and all of these studies affect the corporate image in positive frame.